Production of the Public Area Through an Approach to the Farmer´s Market: New Directions in the Use of the Street (Revista Rupturas, 2017)
The current document addresses the discussion about the social construction of space, specifically about the production of public space in an ephemeral space-time within the urban structure as the farmer's market. It seeks to defend the premise that public space will be appropriate; used; that convenes and dynamizes the city without necessarily being a space defined and conceived for such purposes. The work is constructed through observations and interviews at the farmer's market in the Heredia´s Central Canton, as well as triangulations with various theoretical references.
Keywords: Public area; social production of urban space; appropiation; encounter